2007
DOI: 10.1111/j.1463-6395.2007.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spermatozoa of scolecophidian snakes (Lepidosauria, Squamata)

Abstract: Tavares-Bastos, L., Cunha, L.D., Colli, G.R. and Báo, S.N. 2007. Ultrastructure of spermatozoa of scolecophidian snakes (Lepidosauria, Squamata). -Acta Zoologica (Stockholm) 88 : [189][190][191][192][193][194][195][196][197] We provide a detailed description of the sperm ultrastructure of three species of scolecophidian snakes, Leptotyphlops koppesi (Leptotyphlopidae), Typhlops reticulatus (Typhlopidae) and Liotyphlops beui (Anomalepididae), and make comparisons with the spermatozoa of Ramphotyphlops waitii (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…A single perforatorium within the subacrosomal space has been described as unique for squamates (Teixeira et al. 1999a,c; Tavares‐Bastos et al. 2007; Tourmente et al.…”
Section: Discussionmentioning
confidence: 99%
“…A single perforatorium within the subacrosomal space has been described as unique for squamates (Teixeira et al. 1999a,c; Tavares‐Bastos et al. 2007; Tourmente et al.…”
Section: Discussionmentioning
confidence: 99%
“…As early elongation begins in Agkistrodon piscivorus, it becomes apparent that the acrosome complex is highly compartmentalized, which is common in most squamates (Healy and Jamieson, 1994;Harding et al, 1995;Jamieson and Scheltinga, 1994;Jamieson et al, 1996;Tavares et al, 2007). This complex compartmentalization has been suggested to aid in the release of hydrolytic enzymes that penetrate the outer layers of the ovum during fertilization (Talbot, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first ultrastructural description of a snake spermatozoon by Furieri (1965), multiple studies have been conducted to determine the cytological similarities and differences of the spermatozoa within Serpentes (References in Cunha et al 2008 andTavares-Bastos et al 2008). Only a handful of these studies have attempted to put these data into a phylogenetic context; Tavares-Bastos et al Õs (2008) is the most recent study to map snake sperm traits (Jamieson and Koehler 1994;Harding et al 1995;Jamieson 1995;Jamieson 1999;Oliver et al 1996;Tourmente et al 2006;Tavares-Bastos et al 2007. Tavares-Bastos et al (2008) concluded that multiple characters such as a dense collar in the neck region and mitochondria shape as sinuous tubes in oblique section are proposed synapomorphies in Serpentes, and the ultrastructural data provided by Cunha et al (2008) and Tourmente et al (2008) corroborated these findings.…”
Section: Introductionmentioning
confidence: 99%